MEGA-PROJECT OF THE SOUTHERN FEDERAL UNIVERSITY - Sergey I. Kolesnikov (Высшее образование в России)
The Southern Federal University serves as an effective platform for consolidation of education, enlightenment, science, innovations and management in the field ofa sustainable development ofthe Azov-Black Sea basin. Implementation ofthe mega-project gives synergetic effect in the solution of economic, social and environmental problems of the region and maintenance of its sustainable development.